Legal Policy Model for Handling Violence Among Youth Motorcycle Gangs in Lhokseumawe City - Sari Yulis; Muhammad Rudi Syahputra; Muksalmina; Thoriq Dwiansah (Journal of Law, Politic and Humanities, 2025)
Criminal acts committed by youth motorcycle gangs have become a serious concern in many cities across Indonesia, including Lhokseumawe. Over recent years, Lhokseumawe has faced numerous criminal cases linked to these gangs, such as brawls, slashings, and muggings that disrupt public safety and road users. Despite various measures implemented by the Lhokseumawe City Government and Forkompimda, including curfews and night raids by Satpol PP, WH, and the Police, these efforts have yielded limited results. Many apprehended gang members repeatedly return to criminal activities, highlighting the ineffectiveness of current strategies. A new policy model is urgently needed to address this issue and ensure community safety. This research aims to propose a new preventive policy for the Lhokseumawe City Government. Using an empirical juridical method with a qualitative approach, the study examines field data and existing regulations. Laws governing juvenile involvement in motorcycle gangs include the 1945 Constitution, the Criminal Code, and laws on child protection and juvenile justice. Key factors driving gang involvement include lack of parental guidance, negative social environments, and restricted educational opportunities. Effective handling requires a dual approach: prevention through education, patrols, and social outreach, alongside repressive and rehabilitative measures to help reintegrate affected youth into society.